Proceedings of the 21st International Conference on World Wide Web 2012
DOI: 10.1145/2187836.2187919
|View full text |Cite
|
Sign up to set email alerts
|

Are web users really Markovian?

Abstract: User modeling on the Web has rested on the fundamental assumption of Markovian behavior -a user's next action depends only on her current state, and not the history leading up to the current state. This forms the underpinning of PageRank web ranking, as well as a number of techniques for targeting advertising to users. In this work we examine the validity of this assumption, using data from a number of Web settings. Our main result invokes statistical order estimation tests for Markov chains to establish that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 21 publications
2
83
1
Order By: Relevance
“…In principle, we could go to any order n for higher accuracy. In practice, however, higher-order Markov models are more complex and demand many long pathways to statistically separate real effects of memory from insufficient data 15 . For the air-traffic data, we have enough long pathways to measure the entropy rate of a higher-order Markov model.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In principle, we could go to any order n for higher accuracy. In practice, however, higher-order Markov models are more complex and demand many long pathways to statistically separate real effects of memory from insufficient data 15 . For the air-traffic data, we have enough long pathways to measure the entropy rate of a higher-order Markov model.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work has indicated that a first-order Markov model may fail to adequately predict real dynamics 15,20,23,26 . That is, real dynamics often have at least one-step memory, which conventional network analysis cannot capture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inspired by these questions, we investigate the evolution properties of online user preference diversity, where the preference diversity is measured by the variation coefficient. Firstly, we rescale each user life span to an standard time interval (see Methods), which has been used for the domain analysis of various online settings [32][33][34][35]. Comparing with the null model, the empirical results indicate that, for movies and reviews, the diversity of user preference increases initially and then decreases to a small value.…”
Section: Introductionmentioning
confidence: 99%